Radiation sensitization of the idle voltage spectrum in the photoactive layers of the C₆₀ molecules and squaraine dyes DBSQ - Gaponov, А.М.; Pavlenko, О.L.; Dmytrenko, O.P.; Pinchuk-Rugal, Т.М.; Busko, Т.О.; Pundyk, I.P.; Onanko, A.P.; Alieksandrov, M.A.; Kulish, M.P. (Вопросы атомной науки и техники, 2019)
Quantum-chemical calculations of geometry, charge transfer, energy states, localization of molecular orbitals, optical transitions for complexes of fullerene C₆₀ molecules and DBSQ squaraine dyes were obtained. Optical absorption spectra of C₆₀-DBSQ two-layer films are investigated. It is shown that the films form J-aggregates of dye and complexes with charge transfer C₆₀-DBSQ on the interface. The presence of these complexes leads to the complex structure of the idle voltage spectra. The emergence as a result of high-energy electron irradiation (Ee = 1.8 MeV) with an absorption dose of 2.0 MRad [2+2]-the cyclic connection between fullerenes and dye significantly affects the formation of complexes with charge transfer. The indicated effect results in radiation sensitization of the idle voltage spectra, which manifests itself in the hypsochromic shift of its bands and the modification of the photosensitivity of the photovoltaic cells. Проведено квантово-хімічні розрахунки геометрії, переносу зарядів, енергетичних станів, локалізації молекулярних орбіталей, оптичних переходів для комплексів молекул фулеренів C₆₀ та сквараїнових барвників DBSQ. Досліджено спектри оптичного поглинання двошарових плівок C₆₀–DBSQ. Показано, що в плівках формуються J-агрегати барвника та комплекси з перенесенням зарядів C₆₀–DBSQ на інтерфейсі. Наявність вказаних комплексів призводить до складної будови спектрів напруги холостого ходу. Виникнення в результаті високоенергетичного електронного опромінення (Ее=1,8 МеВ) з дозою поглинання 2,0 МРад [2+2]-циклопід’єднання між фулеренами і барвником істотно впливає на формування комплексів з перенесенням зарядів. Вказаний вплив призводить до радіаційної сенсибілізації спектра напруги холостого ходу, яка проявляється в гіпсохромному зсуві її смуг та модифікації фоточутливості фотовольтаїчних комірок. Проведены квантово-химические расчеты геометрии, переноса зарядов, энергетических состояний, локализации молекулярных орбиталей, оптических переходов для комплексов молекул фуллеренов C₆₀ и сквараиновых красителей DBSQ. Исследованы спектры оптического поглощения двухслойных пленок C₆₀– DBSQ. Показано, что в пленках формируются J-агрегаты красителя и комплексы с переносом зарядов C₆₀– DBSQ на интерфейсе. Наличие указанных комплексов приводит к сложному строению спектров напряжения холостого хода. Возникновение в результате высокоэнергетического электронного облучения (Ее=1,8 МэВ) с дозой поглощения 2,0 МРад [2+2]-циклоприсоединения между фуллеренами и красителем существенно влияет на формирование комплексов с переносом зарядов. Указанное воздействие приводит к радиационной сенсибилизации спектра напряжения холостого хода, которая проявляется в гибсохромном сдвиге ее полос и модификации фоточувствительности фотовольтаических ячеек.